O corpo ideal e a cultura fitness : configurações de um estilo de vida - Costa, Neuza Cristina Gomes da (2019)
This is a qualitative study about the modified body by sportive techniques, specifically by working out and crossfit, which characterizes a new corporeality and allows comprehending the contemporary culture through the understanding about the fitness culture. The methodology consisted in participant observation in a gym and box of crossfit for a year; interview with eight practitioner of these modalities, which criteria of inclusion was to have a modified body in terms of muscled body; interview with two sportive nutritionists because it was considered the alimentation a fundamental matter in the daily life of fitness. The theoretic perspective was based in social studies about the body and body change, in literature about gender, alimentation and medicalization and studies related to working out at the gym, practicing crossfit and other physical techniques as a way of modifying the body. I searched to demonstrate fitness as a field, among others in society; as an interpretable symbolic universe, which characterizes it as a culture and a specific way of living. The modified body allows the subject an identity and a (re)born of a new Me, ruled in a disciplinarian ethics and a higher managements of the self and the own body. This research calls the attention to the social effects of the fitness culture, because, as it is still a phenomenon in development, several aspects need to follow, such as the matter of medicalization of the body and the “creation” of a hormonal body from new speeches of know-power of the medical area and the indiscriminate use of anabolizer. Besides the comprehension of the amplified concept of health, that is related to the esthetics and which must be considered by the professionals of health that work with this public.